The Quality of Family Life and Its Relationship to Irrational Thoughts Among High School Students - A Field Study in Latakia City - شغري فاطمة; ليلى شريف; هنادي حسون (Latakia University Journal - Arts and Humanities Sciences Series, 2025)
The research aimed to identify the level of quality of family life among students of the general secondary education stage Latakia City, and the level of irrational thoughts they have, also to study the relationship between them. To achieve the purpose of the research, the descriptive analytical approach was used, and the research sample included (544) students, and the quality of family life scale was applied, which consisted of (52) items, and the irrational thoughts scale, which consisted of (48) items. The research aimed to identify the level of quality of family life among students of the general secondary education stage Latakia City, and the level of irrational thoughts they have, also to study the relationship between them. To achieve the purpose of the research, the descriptive analytical approach was used, and the research sample included (544) students, and the quality of family life scale was applied, which consisted of (52) items, and the irrational thoughts scale, which consisted of (48) items. The research was found that the level of quality of family life among students of the general secondary education stage Latakia City was middle, and the level of irrational thoughts they have is high, and the existence of a strong inverse relationship between the quality of family life and irrational thoughts among students of the general secondary education stage Latakia City, and the absence of a statistically significant difference in the level of quality of family life among students of the general secondary education stage Latakia City according to the (sex and branch) variables, and there is a statistically significant difference in the level of irrational thoughts they have according to the gender variable in favor of females, and according to the branch variable in favor of the scientific branch.